2013
DOI: 10.1590/1414-431x20132626
|View full text |Cite
|
Sign up to set email alerts
|

Limb immobilization alters functional electrophysiological parameters of sciatic nerve

Abstract: Immobilization, used in clinical practice to treat traumatologic problems, causes changes in muscle, but it is not known whether changes also occur in nerves. We investigated the effects of immobilization on excitability and compound action potential (CAP) and the ultrastructure of the rat sciatic nerve. Fourteen days after immobilization of the right leg of adult male Wistar rats (n=34), animals were killed and the right sciatic nerve was dissected and mounted in a moist chamber. Nerves were stimulated at a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 20 publications
0
13
0
1
Order By: Relevance
“…A previous study about acute intermittent jumping exercise in rats showed an increase in glucose levels and decreased hepatic glycogen levels (Romijn et al, 1993), corroborating with the data obtained in this study. Blood glucose control is essential to the functions of glucose dependent tissues, maintained through consumption of carbohydrates, glycogenolysis and gluconeogenesis (Alves et al, 2013). Exercise increases the oxidation of muscle glycogen (Rogatto et al, 2004), and the reduction of liver glycogen evidenced in this study may be related to higher consumption of muscle glycogen during exercise or as a replacement strategy for muscle glycogen.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…A previous study about acute intermittent jumping exercise in rats showed an increase in glucose levels and decreased hepatic glycogen levels (Romijn et al, 1993), corroborating with the data obtained in this study. Blood glucose control is essential to the functions of glucose dependent tissues, maintained through consumption of carbohydrates, glycogenolysis and gluconeogenesis (Alves et al, 2013). Exercise increases the oxidation of muscle glycogen (Rogatto et al, 2004), and the reduction of liver glycogen evidenced in this study may be related to higher consumption of muscle glycogen during exercise or as a replacement strategy for muscle glycogen.…”
Section: Discussionmentioning
confidence: 59%
“…These data are consistent with previous studies, showing that a short period of disuse by immobilization generates weight reduction (Carvalho et al, 2014;Santos Júnior et al, 2010), reduction in muscle length (Carvalho et al, 2014) and contractile capacity (Santos Júnior et al, 2015). It is known that disuse by immobilization promotes several morphological and physiological changes (Alves et al, 2013) and it acts directly in the muscle tone loss, leading to muscle atrophy (Santos Júnior et al, 2010). Two weeks of immobilization can cause loss of myofibrils and decrease of the size of muscle fibers (Ploug et al, 1995), changes in the morphology of the fibers and muscle mechanics .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both situations may limit the patients' full abilities such as their locomotion and some activities of daily life 1,2 . Small periods of movement restriction, even short-term ones, can lead to several damages to the immobilized region 3 , including disorders in various body segments and organic systems, such as circulatory impairments 1 , ligament alterations 4 , increase of the connective issue 5 , edema 6 , articular rigidity 4 , muscle hypertrophy and atrophy 7 and reduction in bone mineral density 3,8 . In general, depending on the immobilized region and the restraint time, the respiratory system can be compromised.…”
Section: Introductionmentioning
confidence: 99%
“…These damages in the mechanical structure of the diaphragm and the consequent reduction of diaphragmatic movement and thoracic excursion can cause an increase in the mechanical resistance and a decrease of the pulmonary ventilation, leading to atelectasies and pneumonias 9 . Several studies approach the impact of immobilization on the locomotor system [1][2][3]6,7 ; however, little is known about the respiratory system regarding the effects of devices that constrain the torso movement. In this context, the present study examined the impact that the restriction of abdominal movement from an experimental model containing multiple motor limitations can promote on the structure and function of the respiratory system and whether they are reversible with recruitment maneuver.…”
Section: Introductionmentioning
confidence: 99%